(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Fats and oils play a crucial role in leather and textile manufacturing, serving as essential components in various processes such as softening, lubrication, and dyeing. This study explores the chemical and physical mechanisms by which these substances contribute to leather and textile processing. The review covers fatliquoring in leather production, the role of fats in fabric softening, and the advantages of synthetic versus natural oils in textile applications. Recent advancements in environmentally friendly alternatives and sustainable production methods are also discussed. The findings suggest that continuous innovation in fat and oil usage can enhance the efficiency, durability, and sustainability of leather and textile products.